A revised method for determining existing acidity in re-flooded acid sulfate soils. (January 2015) - Johnston, Scott G.; Burton, Edward D.; Hagan, Roslyn; Aaso, Thor; Tuckerman, Gerard
Highlights: We assess an alternate method for TAA (H + ) in re-flooded acid sulfate soil. The method uses wet sediment with anoxic extraction and avoids oven-drying. The method is free from false-positive TAA that undermines the standard approach. Overestimated TAA is poorly correlated with loss in RIS species/gain in SO4 2− . Overestimated TAA appears related to oven-drying induced changes in Fe speciation. Abstract: Titratable actual acidity (TAA) is a technique commonly used to estimate the existing pool of exchangeable H + in acid sulfate soils (ASS). A widely adopted version of the TAA method involves titrating a 1M KCl suspension of oven-dry soil (1:40) with NaOH to a known pH endpoint. However, when ASS are subject to long term re-flooding during wetland remediation, former sulfuric horizons can develop substantial quantities of porewater Fe 2+, non-sulfidic solid-phase Fe(II) and a variety of reduced inorganic sulfur (RIS) species (e.g. pyrite, mackinawite, greigite and elemental sulfur). For these sediments, an oven-drying approach may induce oxidation of the abundant Fe(II) and/or reactive RIS species, thereby generating H + and leading to overestimation of existing in situ exchangeable H + . In this study, we compare TAA via the standard approach (1M KCl; 1:40; oven-dry soil, 4 hr extract; TAAD ) with an identical O2 -free extraction approach using wet-sediment (TAAW ). We apply both methods to former sulfuric horizon sediments from freshwater re-flooded ASS wetlands. There are significant ( α  = 0.01) differences (up to 12×) between TAA measured by the two methods, with the oven-dried standard approach overestimating TAA relative to the wet, O2 -free approach in 85% of cases. Despite the fact that all AVS-S and some S(0) was oxidised during the oven-drying process, the increases in TAA (TAAD –TAAW ) show very weak correlation(s) with corresponding losses in RIS species or increases in water soluble sulfate and KCl extractable sulfate. However, oven-drying caused substantial loss of 1M KCl exchangeable Fe(II) and 1 M HCl-extractable Fe(II) and led to large increases in 1 M HCl-extractable Fe(III). These changes in Fe fractions displayed strong positive linear correlation ( α  = 0.01) with increases in TAA. Although this is not evidence of causality, it suggests that oxidation of Fe(II) species are playing an important role in the development of additional exchangeable H + and may be largely responsible for the contrasting TAA derived by the two methods. The differences in TAA between the two methods are greatest in organic-rich surface sediments and are significantly positively correlated with total organic carbon content. These findings have major implications for accurately assessing TAA in re-flooded ASS wetlands.